2009
DOI: 10.4238/vol8-4gmr687
|View full text |Cite
|
Sign up to set email alerts
|

XRCC1 polymorphisms and haplotypes in Mexican patients with acute lymphoblastic leukemia

Abstract: We examined the influence of the Arg194Trp, Arg280His, and Arg399Gln polymorphisms of XRCC1 (X-ray repair cross-complementing group 1) on the development of childhood acute lymphoblastic leukemia (ALL) in 120 ALL patients and 120 controls in Mexico. All of them were genotyped for these polymorphisms, using polymerase chain reaction. No significant differences in allele and genotype frequencies for any polymorphism were observed between patients and controls. Estimation of haplotypes showed the eight expected h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Finally, it has been revealed that XRCC1 Arg194Trp SNP (rs1799782) is a functional polymorphism and could affect the XRCC1 role, decrease the kinetics of repair mechanism, and influence susceptibility to cancer [25,26]. The role of XRCC1 polymorphisms in susceptibility to acute myeloid leukemia (AML) [27][28][29], acute lymphoblastic leukemia [30], chronic lymphocytic leukemia [31], and lymphoma [32] have been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it has been revealed that XRCC1 Arg194Trp SNP (rs1799782) is a functional polymorphism and could affect the XRCC1 role, decrease the kinetics of repair mechanism, and influence susceptibility to cancer [25,26]. The role of XRCC1 polymorphisms in susceptibility to acute myeloid leukemia (AML) [27][28][29], acute lymphoblastic leukemia [30], chronic lymphocytic leukemia [31], and lymphoma [32] have been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports in human populations suggested the 399Gln variant of XRCC1 was associated with greater DNA and chromosomal damage (Yoon, et al, 2011). It has been suggested that changes in the XRCC1 protein, mainly in amino acid 399, increase the susceptibility for tumor development via genomic instability (Meza-Espinoza, et al, 2009). Nevertheless, another study did not find any effect of the Arg399Gln polymorphisms with regard to DNA damage (Pastorelli et al, 2002), even though it is not well known whether these polymorphisms produce a functional change in the protein.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, polymorphism XRCC1 Arg194Trp, has been found to have a protective effect in Thais (Pakakasama et al 2007), while opposite results have been found in another study (Joseph et al 2005). Moreover, several XRRC1 haplotypes have been related to ALL; haplotype B, as well as C, have been associated with an increased ALL risk (Meza-Espinoza et al 2009, Pakakasama et al 2007). On the other hand, polymorphisms of Nucleotide Excision Repair genes have also been investigated in ALL in a few studies.…”
Section: Acute Lymphoblastic Leukemia (All)mentioning
confidence: 94%
“…Several polymorphisms have been implicated, but results are somewhat conflicting, probably because of the different ethnic groups involved in each study. Thus, polymorphism XRCC1 Arg399Gln has been associated with increased risk of childhood ALL, in Indians (Joseph et al 2005), Chinese (Zhu et al 2005) and Thais (Pakakasama et al 2007), but no correlation was found in Mexican (Meza-Espinoza et al 2009), Brazilian (da Silva Silveira et al 2009) and Turkish children (Batar et al 2009). Perhaps this polymorphism has a stronger effect or a higher penetrance in Asian populations.…”
Section: Acute Lymphoblastic Leukemia (All)mentioning
confidence: 99%